2014
DOI: 10.18410/jebmh/2014/191
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Study of Anterior Talofibular Ligament of Ankle

Abstract: Ankle joint (talocrural) is a hinge joint. The ligaments of this joint are medial and lateral collateral ligaments. Medial deltoid ligament has superficial and deep components. Lateral collateral ligament has Anterior Talofibular (ATFL), Calcaneofibular (CFL) and Posterior Talofibular ligaments (PTFL) as three discrete parts. These two major ligamentous complexes are the main stabilizers of ankle joint which are appreciated both in MRI and cadaveric dissections. Ankle sprains are most common in athletes and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For the latter author [17], who worked on 44 ankles, the variation of the final insertion led to a modification of the angle of the CFL with the sagittal plane; his knowledge is interesting in the radiological diagnosis of ligamentous damage. According to the same authors, the orientation of the ligament also changes depending on the position of the talus, in varus or valgus, which could be a factor of instability and predispose to ankle sprains [7][8][9][10][11][12][13][14][15][16][17]. In the current study, a common insertion with the distal bundle of the ATFL was found in 4% of the cases.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…For the latter author [17], who worked on 44 ankles, the variation of the final insertion led to a modification of the angle of the CFL with the sagittal plane; his knowledge is interesting in the radiological diagnosis of ligamentous damage. According to the same authors, the orientation of the ligament also changes depending on the position of the talus, in varus or valgus, which could be a factor of instability and predispose to ankle sprains [7][8][9][10][11][12][13][14][15][16][17]. In the current study, a common insertion with the distal bundle of the ATFL was found in 4% of the cases.…”
Section: Discussionmentioning
confidence: 51%
“…The CFL shares some features with the distal bundle of the ATFL: 2 isometric ligaments with a common fibular insertion, connected by arciform fibres, and forming a functional and anatomical entity which has been named the lateral fibulotalocalcaneal ligament complex (LFTCL), the lesion of which can cause classical instability [4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations